IDENTIFIKASI FLAVANOID PADA EKSTRAK DAUN MELINJO (GENATUM GENANOM L.) - putriana rahmawati (Universitas Harapan Bangsa Purwokerto, 2017)
Abstract Melinjo plants are an abundant food commodity in Indonesia and have many benefits for consumption ranging from young leaves, flowers, seeds, to the skin. According to Voondan Kueh (1999) all foods derived from melinjo plants have a high nutritional component, such as carbohydrates at 6.60%, protein at 4.20%, calcium at 94.00 mg, vitamins C1, 500 mg and others. The method of this research is Uv-Vis spectrophotometry analysis performed on melinjo leaf samples by measuring the standard absorbance of quercetin flavonoids at a wavelength of 424 nm. The results showed that the content of melinjo leaf flavonoids (Gnetum gnemon L) in Rempoah village was higher than the content of melinjo leaf flavonoids (Gnetum gnemon L) in Dukuh Waluh Village. Rempoah village has a solid soil texture, which causes the roots to easily absorb water from the soil because the particles of soil can hold back the rate of water so that the roots of plants easily absorb water, as a result the plant growth is also getting better. Shown with the content of flavonoid pigments that are better than Dukuh Waluh Village. Whereas in the Dukuh Waluh area the sandy and gravel soil structure results in very weak water binding capacity because the soil particles are too tenuous as a result of lack of water supply so that plant growth is also not good, so there is less flavonoid content. Solid soil causes the roots to easily handle mineral salts and results in increased secondary metabolite content. Keywords: mlinjo, determination, flavanoids